Service Arrangements Colocation Data Center in Indonesia - Nurul Jannati, Fira; Winanti, Atik; Jillena Meliala, Aurora (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to identify, know, and understand arrangements related to agreements Colocation Data Center between Service Provider Companies and Service Users and arrangements related to service services Colocation Data Center in Indonesia. This research uses a normative method with a conceptual approach and a comparative approach sourced from statutory regulations, expert thoughts, and other library materials, supported by interviews, and processed using qualitative data analysis techniques. So we can conclude that the arrangement is related to an agreement Colocation Data Center engender to a new type of agreement because there is a mixture of 2 (two) rental agreements and goods custody agreements which are not recognized in the Civil Code and have not yet been regulated related to services Colocation Data Center in Indonesia. Related to obligations for personal data protection, the position of Service Provider Company is not as a Personal Data Processor due to the hardware on which the data is processed, namely the server not owned by him as reviewed from Law Number 27 of 2022 concerning Protection of Personal Data as well as references for comparative regulations from GDPR and The Digital Personal Data Protection Act. 2023 (No. 22 of 2023).